Modelling and forecasting UK mortgage arrears and possessions - Aron, J; Muellbauer, J (University of Oxford, 2010)
This paper presents new models for aggregate UK data on mortgage possessions (foreclosures) and mortgage arrears (payment delinquencies). The innovations include the treatment of difficuly to observe variations in loan quality and shifts in forbearance policy by lenders, by common latent variables estimated in a system of equations for arrears and possessions, for quarterly data over 1983-2009. A second innovation is the theory-justified use of an estimate of the proportion of mortgages in negative equity, based on an average debt to equity ratio, as one of the key drivers of possessions and arrears. A third is the systematic treatment of measurement bias in the months in arrears measures. Finally, the paper does not impose a proportional long-run relationship between possessions and arrears assumed in the previous UK literature. A range of economic forecast scenarios for forecasts to 2013 reveals the sensitivity of mortgage possessions and arrears to different economic conditions, highlighting potential risks faced by the UK and its mortgage lenders. A comprehensive review of data on arrears and possessions completes the paper.